Wear-resistant amorphous composite coating and application thereof in farm tool blade
By employing a three-stage laser cladding process and the preparation of composite powders, the problems of cracking and porosity in iron-based amorphous composite coatings were solved, resulting in a high-hardness, low-porosity, and excellent wear-resistant and corrosion-resistant coating for agricultural implement blades.
Patent Information
- Application Number
- CN202411822967.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Existing technologies for preparing iron-based amorphous composite coatings suffer from cracks and high porosity, resulting in insufficient wear resistance and corrosion resistance, especially in the application of agricultural implements and blades where wear and corrosion are severe.
A three-stage laser cladding process is adopted, which involves preparing primary and secondary composite powders, combining molybdenum and carbon microspheres to form a dense atomic stacking structure, thereby improving the amorphous formation capability. The three-stage laser cladding process further enhances the density and corrosion resistance of the coating.
The prepared wear-resistant amorphous composite coating has high hardness, low porosity, and no surface cracks, which significantly improves the wear resistance and corrosion resistance of agricultural implement blades and extends their service life.
Smart Images

Figure CN119287361A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite coatings, and in particular to a wear-resistant amorphous composite coating and application thereof in blades of agricultural implements. Background Art
[0002] With the rapid development of agricultural science and technology, the agricultural machinery and equipment industry has also ushered in unprecedented opportunities, and the requirements for the service performance of agricultural machinery and equipment have become increasingly stringent. For agricultural implement blades, due to the relatively poor service conditions of agricultural machinery and equipment, agricultural implement blades need to be in a harsh environment of atmospheric corrosion, soil corrosion and liquid corrosion for a long time. Therefore, wear, corrosion and fatigue fracture have become the main factors for the failure of agricultural implement blades. Especially the wear of agricultural implement blades. According to statistics, more than 80% of agricultural implement blade failures are caused by wear. Because agricultural implement blades will undergo abrasive friction with soil, sand and grass during operation, resulting in a very fast wear rate of agricultural implement blades. Therefore, in the use of agricultural implement blades, passivation, chipping and breakage are prone to occur, which greatly reduces the service life of agricultural implement blades and affects agricultural production.
[0003] Amorphous materials are considered to be the fourth conventional state of matter, along with gas, liquid and solid phases. Amorphous alloys in amorphous materials refer to the condensed state of disordered liquid atoms at room temperature or low temperature when the material is rapidly cooled from liquid or gaseous state because it does not have time to crystallize. The atoms in the amorphous alloy are no longer in long-range order, periodicity and regular arrangement, and there are no grains or grain boundaries of crystalline alloys. Amorphous alloys have excellent mechanical and chemical properties, such as extremely high strength and hardness, excellent wear resistance and corrosion resistance, and have therefore received extensive attention from researchers at home and abroad.
[0004] By utilizing the excellent mechanical and chemical properties of amorphous alloys, amorphous alloys are used as coating materials and applied to agricultural implement blades to improve the wear resistance and corrosion resistance of agricultural implement blades. Considering the poor plastic deformation ability and high brittleness of non-static alloys, the commonly used methods for preparing coating materials are laser cladding, atmospheric plasma spraying, arc spraying, high-speed oxygen-fuel spraying and explosion spraying. Among them, the laser cladding method is to use the high-energy laser beam emitted by the laser to quickly heat the surface of the agricultural implement blade, add powder, and quickly melt the powder pre-placed on the surface of the agricultural implement blade or synchronously fed powder, so as to prepare a high-quality amorphous composite coating. The laser cladding method has the advantages of a small heat-affected zone, the ability of the amorphous composite coating to achieve metallurgical bonding with the agricultural implement blade, and low deformation of the agricultural implement blade caused by cladding. The amorphous composite coating formed by laser cladding contains both atomic stacking structures, which can improve the ability to resist plastic deformation, and certain hard particles and nanocrystals. The hard particles are evenly dispersed and precipitated in the laser cladding layer, resulting in dispersion strengthening. In addition, during the rapid solidification process of the laser cladding layer, the fine grains do not have time to grow into nanocrystals. The grain boundaries in the nanocrystals can produce a strengthening effect, thereby improving the hardness and wear resistance of the amorphous composite coating.
[0005] Iron-based amorphous alloy is an amorphous alloy with iron as the main element and a small amount of other metal elements added. During the preparation, the iron-containing elements are melted in liquid form and cooled into shape through rapid cooling technology. Iron-based amorphous alloy has extremely high hardness, excellent wear resistance and corrosion resistance, and low cost. It has broad application prospects. More and more researchers in the field of agricultural machinery and equipment are using iron-based amorphous alloys in coating materials for agricultural tool blades.
[0006] However, when preparing iron-based amorphous composite coatings by laser cladding, the following problems exist: First, the laser cladding method is a process of rapid heating and rapid cooling. In a short period of time, the iron-based amorphous alloy and the farm tool blade melt into a liquid state, and then transform from a liquid state into a solid state. In the above process, the iron-based amorphous alloy is constrained by the outside world to produce internal stress. When the internal stress exceeds the yield strength of the iron-based amorphous alloy, cracks will occur. Among them, the internal stress mainly includes thermal stress, microstructural stress and constraint stress. Therefore, the iron-based amorphous composite coating prepared by laser cladding has crack problems and a high porosity problem; second, although the iron-based amorphous alloy has strong corrosion resistance, the presence of cracks in the coating material of the farm tool blade will cause crevice corrosion, and electrochemical corrosion will occur inside the crack and on the entire surface outside. The anode reaction is metal ionization, and the cathode reaction is oxygen reduction. As the corrosion process continues, the oxygen inside the crack is constantly consumed, and the oxygen outside the crack is replenished at any time to maintain the corrosion. The metal ions inside the crack continue to accumulate. In order to maintain the charge balance, negative ions are enriched inside the crack, among which the negative ions include chloride ions, which leads to the concentration of metal ions and the enrichment of chloride ions inside the crack, generating soluble metal chlorides. The metal chlorides are hydrolyzed to generate insoluble metal hydroxides and free acids, which leads to a decrease in the pH inside the crack, further promoting the dissolution of the anode metal, and causing more chloride ions to migrate from the outside of the crack to the inside of the crack, further promoting the corrosion. This cycle leads to the problem of poor corrosion resistance of the iron-based amorphous composite coating prepared by laser cladding.
[0007] In view of the above problems, according to the search of existing solutions, the inventor tried the following methods: first, by laser remelting the iron-based amorphous composite coating, the cracks in the iron-based amorphous composite coating are reduced, and the porosity of the iron-based amorphous composite coating is reduced; second, after the laser cladding powder is prepared by gas atomization, molybdenum is added to the laser cladding powder. Molybdenum and iron have larger atomic sizes, and there is a larger atomic size difference compared with boron and carbon, so that the atomic stacking structure is more compact. With the addition of molybdenum, a larger gap can be provided, which is conducive to the embedding of elements with small atomic sizes, thereby increasing the disordered stacking of the alloy liquid phase, which in turn causes a larger structural distortion, and inhibits the diffusion of atoms, further improving the amorphous forming ability. Moreover, molybdenum has the characteristics of self-passivation, and can form a stable passivation film, further improving the corrosion resistance of the iron-based amorphous composite coating.
[0008] However, the above method has the following problems: First, laser remelting will increase the dislocation density, achieve microstructural densification and grain refinement, but after laser remelting, transgranular cracks will appear in the iron-based amorphous composite coating, and transgranular cracks will lead to a decrease in the wear resistance of the iron-based amorphous composite coating; Second, experiments have shown that when the mass fraction of molybdenum added to the laser cladding powder is greater than 1.5%, the morphology of the middle part of the amorphous composite coating is different from that of the surface layer and the layer close to the substrate, and it is rich in a large number of grains and second phases, showing a wide band shape, while there are no obvious grains and second phases on the surface layer of the amorphous composite coating and in the layer close to the substrate of the amorphous composite coating. Local magnification shows that white block grains are scattered, superimposed or staggered together, and densely packed white dot-like phases can be observed around the white block grains. Composition analysis shows that the white block grains are molybdenum and iron. With the increase of molybdenum addition, the white block grains are enriched, the grains increase, and molybdenum-rich dendrites appear, resulting in a decrease in the hardness and wear resistance of the iron-based amorphous composite coating. Therefore, the mass fraction of molybdenum added to the laser cladding powder should be controlled within 1.5%. However, the smaller the molybdenum content, the worse the density of the passivation film formed, and the less obvious the effect of improving the corrosion resistance of the iron-based amorphous composite coating. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides a wear-resistant amorphous composite coating and its application in agricultural tool blades. The wear-resistant amorphous composite coating of the present invention has high hardness, good wear resistance and corrosion resistance, no cracks on the surface, and low porosity.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A wear-resistant amorphous composite coating, the preparation method of which comprises the following steps: preparing a primary composite powder, pre-treating, laser cladding once, laser cladding twice, preparing a secondary composite powder, laser cladding three times; The preparation of the primary composite powder comprises the following steps: preparing carbon microspheres, compounding, mixing, and primary compounding; The carbon microspheres are prepared by adding sucrose, boric acid and deionized water into a reactor lined with polytetrafluoroethylene, controlling the stirring speed of the reactor to 40-60 rpm, stirring at room temperature for 20-30 min, sealing the reactor, adding the reactor into an oven, controlling the temperature of the oven to 120-130° C., taking out the reactor from the oven after 10-11 hours, cooling it naturally to room temperature, transferring the product in the reactor into a centrifuge, controlling the centrifugal speed of the centrifuge to 7000-8000 rpm, centrifuging for 20-25 min, taking the precipitate, washing it with deionized water for 4-6 times, and vacuum drying it at 80-90° C. to obtain carbon microspheres; In the preparation of the carbon microspheres, the dosage ratio of sucrose, boric acid and deionized water is 155-165 g: 6-6.5 g: 1300-1400 mL; The composite comprises mixing carbon microspheres and deionized water, adding the mixture to an ultrasonic oscillator, and ultrasonically oscillating for 30-40 minutes. Then, sodium molybdate dihydrate is added, and ultrasonically oscillating is continued for 30-40 minutes. Then, the mixture and sodium borohydride are added to a reactor, and the stirring speed of the reactor is controlled to 40-60 rpm. The mixture is stirred at room temperature for 50-60 minutes. The product in the reactor is transferred to a centrifuge, and the centrifugal speed of the centrifuge is controlled to 7000-8000 rpm. The mixture is centrifuged for 20-25 minutes. The precipitate is taken, washed with deionized water for 4-6 times, and vacuum dried at 80-90° C. to obtain composite microspheres. In the composite, the usage ratio of carbon microspheres, deionized water, sodium molybdate dihydrate, and sodium borohydride is 40-42 g: 4000-4500 mL: 70-80 g: 60-65 g; The frequency of the ultrasonic oscillation is 20-25kHz; The mixing, after the iron powder, molybdenum powder, chromium powder, boron powder, carbon powder and yttrium powder are uniformly mixed, is added into a vacuum melting furnace for gas atomization, nitrogen is used as an atomizing gas, the atomization pressure in the gas atomization is controlled to 4-5MPa, and sieving is performed to obtain laser cladding powder; In the mixture, the mass ratio of iron powder, molybdenum powder, chromium powder, boron powder, carbon powder and yttrium powder is 54-56:17-18:15-15.5:1.2-1.3:3.4-3.6:3.4-3.6; The mass purity of the iron powder is 99.99%; The mass purity of the molybdenum powder is 99.9%; The mass purity of the chromium powder is 99.99%; The mass purity of the boron powder is 99.9%; The mass purity of the carbon powder is 99.99%; The mass purity of the yttrium powder is 99.5%; The particle size of the cladding powder is 150-400 mesh; The first-level composite comprises mixing the laser cladding powder, molybdenum powder and composite microspheres, adding the mixture into a ball mill mixer for ball milling, then taking the mixture out, adding the mixture into a drying oven for drying, and then taking the mixture out to obtain the first-level composite powder; In the primary composite, the mass ratio of laser cladding powder, molybdenum powder and composite microspheres is 100:2.1-2.2:2.1-2.2; The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; The ball-to-material mass ratio in the ball mill is 2-3:1, the rotation speed is 300-350rpm, and the ball milling time is 2-2.5h; The temperature during the drying is 110-120° C. and the drying time is 2-2.5 hours; The pretreatment includes grinding the surface of the No. 20 steel plate flat with an angle grinder and a wire brush, cleaning the surface impurities and oxide scale, and wiping it with alcohol to obtain a pretreated steel plate; The primary laser cladding comprises spreading the primary composite powder on the pretreated steel plate, using a pulsed laser for laser cladding, and cleaning the surface of the cladding layer with a wire brush after the laser cladding is completed, and cooling the layer naturally in the air to obtain a primary laser cladding material; In the first laser cladding, the thickness of the first-level composite powder is 0.4-0.42 mm; The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min; The secondary laser cladding comprises spreading the primary composite powder on the pretreated steel plate, using a pulsed laser for laser cladding, and cleaning the surface of the cladding layer with a wire brush after the laser cladding is completed, and cooling the layer naturally in the air to obtain a secondary laser cladding material; In the secondary laser cladding, the thickness of the first-level composite powder is 0.3-0.32 mm; The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min; The second-level composite powder is prepared by mixing the first-level composite powder and the composite microspheres, adding the first-level composite powder and the composite microspheres into a ball mill mixer for ball milling, then taking them out, adding them into a drying oven for drying, and then taking them out to obtain the second-level composite powder; In the preparation of the secondary composite powder, the mass ratio of the primary composite powder to the composite microspheres is 104.2-104.4:0.9-1; The ball-to-material mass ratio in the ball mill is 2-3:1, the rotation speed is 300-350rpm, and the ball milling time is 1.5-2h; The temperature during the drying is 110-120°C and the drying time is 1.5-2h; The three laser cladding processes are to spread the secondary composite powder on the pretreated steel plate, use a pulsed laser for laser cladding, and after the laser cladding is completed, use a wire brush to clean the surface of the cladding layer, and cool it naturally in the air to obtain a wear-resistant amorphous composite coating; In the three laser cladding processes, the thickness of the secondary composite powder is 0.4-0.42 mm. The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min.
[0011] An application of the aforementioned wear-resistant amorphous composite coating in agricultural tool blades.
[0012] Compared with the prior art, the present invention has the following beneficial effects: (1) The wear-resistant amorphous composite coating of the present invention uses a primary composite powder and a secondary composite powder in the preparation. In the preparation of the primary composite powder, molybdenum powder and composite microspheres are added to the laser cladding powder. When preparing the composite microspheres, sucrose and boric acid are first used as raw materials to prepare carbon microspheres, and then the carbon microspheres are mixed with sodium molybdate dihydrate, and the sodium molybdate dihydrate is loaded on the surface of the carbon microspheres. Then, sodium borohydride is used to reduce the sodium molybdate dihydrate to obtain carbon microspheres loaded with molybdenum elements. After adding molybdenum powder and composite microspheres to the laser cladding powder, the composite microspheres have a small particle size and can be evenly attached to the laser cladding particles and the surface of the molybdenum powder, thereby achieving uniform dispersion of molybdenum and carbon elements. During the laser cladding process, the molybdenum and carbon elements in the composite microspheres can form a denser atomic stacking structure and achieve pre-embedding of carbon elements, thereby increasing The disordered stacking property of alloy liquid combination is added, thereby improving the amorphous forming ability, promoting the uniform dispersion of molybdenum powder, avoiding the aggregation of white block grains formed by molybdenum elements, improving the hardness and wear resistance of the iron-based amorphous composite coating, reducing porosity, avoiding the generation of surface cracks, and at the same time increasing the amount of molybdenum elements added, improving the corrosion resistance of the iron-based amorphous composite coating, and through three laser cladding, and increasing the amount of composite microspheres added in the secondary composite powder used in the three laser cladding, that is, increasing the amount of composite microspheres added in the surface layer of the amorphous composite coating, the composite microspheres in the surface layer of the amorphous composite coating can act as an inhibitor, and the carbon in the composite microspheres is combined with the interface of the white block grains formed by molybdenum in the middle of the amorphous composite coating, thereby inhibiting the growth of the white block grains, and further improving the hardness and wear resistance of the iron-based amorphous composite coating; (2) The wear-resistant amorphous composite coating of the present invention has a high hardness, with a Vickers hardness of 1231-1272 HV 0.3 ; (3) The wear-resistant amorphous composite coating of the present invention has a low porosity of 0.75-0.81%; (4) The wear-resistant amorphous composite coating of the present invention has no cracks on its surface; (5) The wear-resistant amorphous composite coating of the present invention has good wear resistance. The wear-resistant amorphous composite coating of the present invention is subjected to a dry sliding friction and wear test. The vertical compressive stress in the dry sliding friction and wear test is controlled to be 100N. A tungsten carbide steel ball is used as a grinding ball. The hardness of the grinding ball is HRA92, the diameter is 9.5mm, the rotation radius is 2mm, the friction time is 60min, the total sliding distance is 77m, and the weight loss is 0.017-0.021g. (6) The wear-resistant amorphous composite coating of the present invention has good wear resistance. The wear-resistant amorphous composite coating of the present invention is subjected to a corrosion resistance test. In the corrosion resistance test, a three-electrode electrochemical workstation is used, a saturated calomel electrode (SCE) is used as a reference electrode, a platinum electrode is used as an auxiliary electrode, and a hydrochloric acid solution with a molar concentration of 1 mol / L is configured as an electrolyte. The self-corrosion current density measured at room temperature is 1.310×10 -5 -1.372×10 -5 A / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a SEM analysis image of the wear-resistant amorphous composite coating prepared in Example 2; Figure 2 This is a SEM analysis image of the wear-resistant amorphous composite coating prepared in Comparative Example 1; Figure 3 This is a SEM analysis image of the wear-resistant amorphous composite coating prepared in Comparative Example 2; Figure 4 X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 1-3; In the figure, the upper curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 3, the middle curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 2, and the lower curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 1. DETAILED DESCRIPTION
[0014] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0015] Example 1 A wear-resistant amorphous composite coating, the preparation method of which is: 1. Preparation of primary composite powder: (1) Preparation of carbon microspheres: 155 g sucrose, 6 g boric acid, and 1300 mL deionized water were added to a polytetrafluoroethylene-lined reactor, the stirring speed of the reactor was controlled to 40 rpm, and the mixture was stirred at room temperature for 20 min. The reactor was sealed and placed in an oven, and the temperature of the oven was controlled to 120 °C. After 10 h, the reactor was removed from the oven and naturally cooled to room temperature. The product in the reactor was transferred to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 7000 rpm. The mixture was centrifuged for 20 min. The precipitate was taken out and washed four times with deionized water, and vacuum dried at 80 °C to obtain carbon microspheres. (2) Compounding: 40 g of carbon microspheres and 4000 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 20 kHz. The ultrasonic oscillator was ultrasonically oscillated for 30 min. 70 g of sodium molybdate dihydrate was added and the ultrasonic oscillation was continued for 30 min. The mixture and 60 g of sodium borohydride were added to a reactor. The stirring speed of the reactor was controlled to 40 rpm. The mixture was stirred at room temperature for 50 min. The product in the reactor was transferred to a centrifuge. The centrifugal speed of the centrifuge was controlled to 7000 rpm. The mixture was centrifuged for 20 min. The precipitate was washed 4 times with deionized water and dried under vacuum at 80 °C to obtain composite microspheres. (3) Mixing: 54 parts of iron powder, 17 parts of molybdenum powder, 15 parts of chromium powder, 1.2 parts of boron powder, 3.4 parts of carbon powder, and 3.4 parts of yttrium powder were mixed evenly by mass, and then added into a vacuum melting furnace for gas atomization. Nitrogen was used as the atomizing gas. The atomization pressure during the gas atomization was controlled to 4 MPa. The powder was sieved to obtain laser cladding powder. The mass purity of the iron powder is 99.99%; The mass purity of the molybdenum powder is 99.9%; The mass purity of the chromium powder is 99.99%; The mass purity of the boron powder is 99.9%; The mass purity of the carbon powder is 99.99%; The mass purity of the yttrium powder is 99.5%; The particle size of the cladding powder is 150 mesh; (4) Primary composite: 100 parts by mass of laser cladding powder, 2.1 parts by mass of molybdenum powder and 2.1 parts by mass of composite microspheres were mixed and added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1 and the rotation speed was controlled to 300 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 110°C. After 2 hours, the mixture was taken out to obtain primary composite powder. The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; 2. Pretreatment: Use an angle grinder and a wire brush to grind the surface of the No. 20 steel plate flat, clean the surface impurities and oxide scale, and wipe it clean with alcohol to obtain the pretreated steel plate; 3. Primary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.4mm, use pulse laser for laser cladding, control the laser output power to 600W, laser duty cycle to 95%, focal length to 400mm, pulse voltage to 260V, pulse frequency to 15Hz, pulse width to 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer, and cool it naturally in the air to obtain a primary laser cladding material; 4. Secondary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.3mm, use pulse laser for laser cladding, control the laser output power to 600W, laser duty cycle to 95%, focal length to 400mm, pulse voltage to 260V, pulse frequency to 15Hz, pulse width to 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain the secondary laser cladding material; 5. Preparation of secondary composite powder: 104.2 parts of primary composite powder and 0.9 parts of composite microspheres were mixed by mass, and then added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1, and the rotation speed was controlled to 300 rpm. After 1.5 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 110°C. After 1.5 hours, the mixture was taken out to obtain secondary composite powder. 6. Three-stage laser cladding: Spread the secondary composite powder on the pretreated steel plate, control the thickness of the powder to be 0.4 mm, use a pulsed laser for laser cladding, control the laser output power in the laser cladding to be 600 W, the laser duty cycle to be 95%, the focal length to be 400 mm, the pulse voltage to be 260 V, the pulse frequency to be 15 Hz, the pulse width to be 2 ms, and the argon flow rate sprayed on the cladding point to be 10 L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain a wear-resistant amorphous composite coating.
[0016] This embodiment also provides an application of the aforementioned wear-resistant amorphous composite coating in agricultural tool blades.
[0017] Example 2 A wear-resistant amorphous composite coating, the preparation method of which is: 1. Preparation of primary composite powder: (1) Preparation of carbon microspheres: 160 g sucrose, 6.2 g boric acid, and 1350 mL deionized water were added to a polytetrafluoroethylene-lined reactor, the stirring speed of the reactor was controlled to 50 rpm, and the mixture was stirred at room temperature for 25 min. The reactor was sealed and placed in an oven, the temperature of the oven was controlled to 125 °C, and after 10.5 h, the reactor was removed from the oven and naturally cooled to room temperature. The product in the reactor was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 8000 rpm, and the mixture was centrifuged for 20 min. The precipitate was taken out and washed with deionized water for 5 times, and vacuum dried at 85 °C to obtain carbon microspheres. (2) Compounding: 41 g of carbon microspheres and 4200 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 20 kHz. The ultrasonic oscillator was ultrasonically oscillated for 35 min. 75 g of sodium molybdate dihydrate was added and the ultrasonic oscillation was continued for 35 min. The mixture and 62 g of sodium borohydride were added to a reactor. The stirring speed of the reactor was controlled to 50 rpm. The mixture was stirred at room temperature for 55 min. The product in the reactor was transferred to a centrifuge. The centrifugal speed of the centrifuge was controlled to 8000 rpm. The mixture was centrifuged for 20 min. The precipitate was washed 5 times with deionized water and vacuum dried at 85 °C to obtain composite microspheres. (3) Mixing: 55 parts of iron powder, 17.5 parts of molybdenum powder, 15.2 parts of chromium powder, 1.2 parts of boron powder, 3.5 parts of carbon powder, and 3.5 parts of yttrium powder were mixed evenly by mass, and then added into a vacuum melting furnace for gas atomization. Nitrogen was used as the atomizing gas. The atomization pressure during gas atomization was controlled to 4.5 MPa. The mixture was sieved to obtain laser cladding powder. The mass purity of the iron powder is 99.99%; The mass purity of the molybdenum powder is 99.9%; The mass purity of the chromium powder is 99.99%; The mass purity of the boron powder is 99.9%; The mass purity of the carbon powder is 99.99%; The mass purity of the yttrium powder is 99.5%; The particle size of the cladding powder is 300 mesh; (4) Primary composite: 100 parts by weight of laser cladding powder, 2.1 parts by weight of molybdenum powder, and 2.1 parts by weight of composite microspheres were mixed and added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1 and the rotation speed was controlled to 300 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 115°C. After 2 hours, the mixture was taken out to obtain a primary composite powder. The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; 2. Pretreatment: Use an angle grinder and a wire brush to grind the surface of the No. 20 steel plate flat, clean the surface impurities and oxide scale, and wipe it clean with alcohol to obtain the pretreated steel plate; 3. Primary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.4 mm, use a pulsed laser for laser cladding, control the laser output power to 600 W, the laser duty cycle to 95%, the focal length to 400 mm, the pulse voltage to 300 V, the pulse frequency to 17 Hz, the pulse width to 2 ms, and the argon flow rate sprayed on the cladding point to be 10 L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain a primary laser cladding material; 4. Secondary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.3mm, use pulse laser for laser cladding, control the laser output power to 600W, laser duty cycle to 95%, focal length to 400mm, pulse voltage to 300V, pulse frequency to 17Hz, pulse width to 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain the secondary laser cladding material; 5. Preparation of secondary composite powder: 104.2 parts of primary composite powder and 1 part of composite microspheres were mixed by mass, and then added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1, and the rotation speed was controlled to 300 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 115°C. After 2 hours, the mixture was taken out to obtain secondary composite powder. 6. Three-stage laser cladding: Spread the secondary composite powder on the pretreated steel plate, control the powder thickness to 0.4 mm, use a pulsed laser for laser cladding, control the laser output power to 600 W, the laser duty cycle to 95%, the focal length to 400 mm, the pulse voltage to 300 V, the pulse frequency to 17 Hz, the pulse width to 2 ms, and the argon flow rate sprayed on the cladding point to be 10 L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain a wear-resistant amorphous composite coating.
[0018] This embodiment also provides an application of the aforementioned wear-resistant amorphous composite coating in agricultural tool blades.
[0019] Example 3 A wear-resistant amorphous composite coating, the preparation method of which is: 1. Preparation of primary composite powder: (1) Preparation of carbon microspheres: 165 g of sucrose, 6.5 g of boric acid, and 1400 mL of deionized water were added to a reactor lined with polytetrafluoroethylene, the stirring speed of the reactor was controlled to 60 rpm, and the mixture was stirred at room temperature for 30 min. The reactor was sealed and placed in an oven, and the temperature of the oven was controlled to 130 °C. After 11 h, the reactor was taken out of the oven and naturally cooled to room temperature. The product in the reactor was transferred to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 8000 rpm. The mixture was centrifuged for 25 min, and the precipitate was taken out and washed with deionized water for 6 times. The precipitate was vacuum dried at 90 °C to obtain carbon microspheres. (2) Compounding: 42 g of carbon microspheres and 4500 mL of deionized water were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 25 kHz. The ultrasonic oscillator was ultrasonically oscillated for 40 min. 80 g of sodium molybdate dihydrate was added and the ultrasonic oscillation was continued for 40 min. The mixture and 65 g of sodium borohydride were added to a reactor. The stirring speed of the reactor was controlled to 60 rpm. The mixture was stirred at room temperature for 60 min. The product in the reactor was transferred to a centrifuge. The centrifugal speed of the centrifuge was controlled to 8000 rpm. The mixture was centrifuged for 25 min. The precipitate was washed 6 times with deionized water and dried under vacuum at 90 °C to obtain composite microspheres. (3) Mixing: 56 parts of iron powder, 18 parts of molybdenum powder, 15.5 parts of chromium powder, 1.3 parts of boron powder, 3.6 parts of carbon powder, and 3.6 parts of yttrium powder were mixed evenly by mass, and then added into a vacuum melting furnace for gas atomization. Nitrogen was used as the atomizing gas. The atomization pressure during the gas atomization was controlled to 5 MPa. The mixture was sieved to obtain laser cladding powder. The mass purity of the iron powder is 99.99%; The mass purity of the molybdenum powder is 99.9%; The mass purity of the chromium powder is 99.99%; The mass purity of the boron powder is 99.9%; The mass purity of the carbon powder is 99.99%; The mass purity of the yttrium powder is 99.5%; The particle size of the cladding powder is 400 mesh; (4) Primary composite: 100 parts by mass of laser cladding powder, 2.2 parts by mass of molybdenum powder and 2.2 parts by mass of composite microspheres were mixed and added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 3:1 and the rotation speed was controlled to 350 rpm. After 2.5 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 120°C. After 2.5 hours, the mixture was taken out to obtain primary composite powder. The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; 2. Pretreatment: Use an angle grinder and a wire brush to grind the surface of the No. 20 steel plate flat, clean the surface impurities and oxide scale, and wipe it clean with alcohol to obtain the pretreated steel plate; 3. Primary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.42mm, use pulse laser for laser cladding, control the laser output power to 600W, laser duty cycle to 95%, focal length to 400mm, pulse voltage to 300V, pulse frequency to 20Hz, pulse width to 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain a primary laser cladding material; 4. Secondary laser cladding: Spread the primary composite powder on the pretreated steel plate, control the powder thickness to 0.32mm, use a pulsed laser for laser cladding, control the laser output power to 600W, the laser duty cycle to 95%, the focal length to 400mm, the pulse voltage to 300V, the pulse frequency to 20Hz, the pulse width to 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain the secondary laser cladding material; 5. Preparation of secondary composite powder: 104.4 parts of primary composite powder and 1 part of composite microspheres were mixed by mass, and then added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 3:1, and the rotation speed was controlled to 350 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 120°C. After 2 hours, the mixture was taken out to obtain secondary composite powder. 6. Three-stage laser cladding: Spread the secondary composite powder on the pretreated steel plate, control the thickness of the powder to be 0.42mm, use a pulsed laser for laser cladding, control the laser output power in the laser cladding to be 600W, the laser duty cycle to be 95%, the focal length to be 400mm, the pulse voltage to be 300V, the pulse frequency to be 20Hz, the pulse width to be 2ms, and the argon flow rate sprayed on the cladding point to be 10L / min. After the laser cladding is completed, use a wire brush to clean the surface of the cladding layer and cool it naturally in the air to obtain a wear-resistant amorphous composite coating.
[0020] This embodiment also provides an application of the aforementioned wear-resistant amorphous composite coating in agricultural tool blades.
[0021] Comparative Example 1 Based on the preparation method of the wear-resistant amorphous composite coating of Example 2, the step (1) of preparing carbon microspheres and the step (2) of compounding in the step (1) of preparing the primary composite powder are omitted, and the addition of composite microspheres is omitted in the step (4) of the primary compounding step; specifically, the step (4) of the primary compounding step is changed to: 100 parts of laser cladding powder and 2.1 parts of molybdenum powder were mixed by weight, and then added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1, and the rotation speed was controlled to 300 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 115°C. After 2 hours, the mixture was taken out to obtain a first-grade composite powder. The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; Accordingly, the preparation of the secondary composite powder in step 5 was also omitted, and an equal amount of the primary composite powder was used to replace the secondary composite powder in the third laser cladding step in step 6.
[0022] The rest of the technical solutions are consistent with those in Example 2.
[0023] Comparative Example 2 Based on the preparation method of the wear-resistant amorphous composite coating of Comparative Example 1, the mass fraction range of molybdenum in the primary composite powder is changed, specifically, the primary composite step (4) is changed to: 100 parts of laser cladding powder and 4.2 parts of molybdenum powder were mixed by weight, and then added to a ball mill mixer for ball milling. The ball-to-material mass ratio in the ball mill was controlled to 2:1, and the rotation speed was controlled to 300 rpm. After 2 hours, the mixture was taken out and added to a drying oven for drying. The temperature during drying was controlled to 115°C. After 2 hours, the mixture was taken out to obtain a first-grade composite powder. The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes.
[0024] The rest of the technical solutions are consistent with those in Comparative Example 1.
[0025] Performance Test 1 The Vickers hardness and porosity of the wear-resistant amorphous composite coatings prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the presence of cracks on the surface of the wear-resistant amorphous composite coatings was observed. The test and observation results are as follows:
[0026] The wear-resistant amorphous composite coatings prepared in Example 2, Comparative Example 1, and Comparative Example 2 were subjected to SEM analysis. When performing the SEM analysis, the cross section of the sample was first processed, specifically grinding, polishing, and etching according to the metallographic analysis sample standard. The cross section of the sample was polished in the order of coarse to fine sandpaper using 600#, 800#, 1000#, and 1200# silicon carbide sandpapers on a grinding machine, respectively. Then, the sample was polished with diamond abrasive paste on a polishing machine, and finally, aqua regia etching solution (the ratio of concentrated hydrochloric acid to concentrated nitric acid was 3:1) was configured to slightly erode the cross section. After 5 minutes, the cross section was cleaned and observed under a SEM scanning electron microscope. The SEM analysis diagram of the wear-resistant amorphous composite coating prepared in Example 2 is shown in FIG. Figure 1 The SEM analysis of the wear-resistant amorphous composite coating prepared in Comparative Example 1 is shown in Figure 2 The SEM analysis of the wear-resistant amorphous composite coating prepared in Comparative Example 2 is shown in Figure 3 ; Depend on Figure 1-3 It can be seen that the wear-resistant amorphous composite coating prepared in Example 2 has a complete and dense overall structure and is well bonded to the substrate. Compared with Example 1, the wear-resistant amorphous composite coating prepared has cracks and white block grains. Compared with Example 2, the wear-resistant amorphous composite coating prepared has cracks and white block grains. Moreover, due to the increase in molybdenum content, the white block grains are larger, indicating that as the molybdenum content increases, the molybdenum grains will become more enriched and the grains will become larger.
[0027] Performance Test 2 The wear-resistant amorphous composite coatings prepared in Examples 1-3 were analyzed by X-ray diffractometer. The samples were processed before testing. Specifically, 180# SiC sandpaper was used for grinding on a grinding machine to obtain a relatively smooth surface, and then the samples were cleaned with alcohol. The diffraction conditions were Cu target, 40KV, 100mA, scanning speed of 8° / min, scanning range 2θ of 10°-90°, step width of 0.02°, and the obtained X-ray diffraction pattern was shown in FIG. Figure 4 As shown, Figure 4 In the figure, the upper curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 3, the middle curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 2, and the lower curve is the X-ray diffraction pattern of the wear-resistant amorphous composite coating prepared in Example 1. Figure 4 It can be seen that broadened diffraction peaks appear when 2θ is about 43°, and sharp crystal peaks are accompanied by the broadened diffraction peaks, indicating that the wear-resistant amorphous composite coatings prepared in Examples 1-3 contain both amorphous phases and nanocrystalline phases.
[0028] Performance Test 3 The wear-resistant amorphous composite coatings prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to dry sliding friction and wear tests, the vertical compressive stress in the dry sliding friction and wear test was controlled to be 100 N, tungsten carbide steel balls were used as grinding balls, the hardness of the grinding balls was HRA92, the diameter was 9.5 mm, the rotation radius was 2 mm, the friction time was 60 min, the total sliding distance was 77 m, and then the weight loss of the wear-resistant amorphous composite coating was tested, and the test results are as follows:
[0029] Performance Test 4 The wear-resistant amorphous composite coatings prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to corrosion resistance tests. In the corrosion resistance tests, a three-electrode electrochemical workstation was used, a saturated calomel electrode (SCE) was used as a reference electrode, a platinum electrode was used as an auxiliary electrode, and a hydrochloric acid solution with a molar concentration of 1 mol / L was configured as an electrolyte. At room temperature, the self-corrosion current density of the wear-resistant amorphous composite coatings prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test results are as follows:
[0030] It can be seen from the results of performance tests 1-4 that, compared with Comparative Example 1 and Comparative Example 2, the wear-resistant amorphous composite coating prepared in Example 2 has higher hardness, better wear resistance and corrosion resistance, lower porosity, and no surface cracks.
[0031] Unless otherwise specified, all percentages used in the present invention are by mass.
[0032] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A wear-resistant amorphous composite coating, characterized in that: The method for preparing the wear-resistant amorphous composite coating comprises the following steps: preparing a primary composite powder, pre-treating, laser cladding once, laser cladding twice, preparing a secondary composite powder, laser cladding three times; The preparation of the primary composite powder comprises the following steps: preparing carbon microspheres, compounding, mixing, and primary compounding; The carbon microspheres are prepared by mixing sucrose, boric acid and deionized water, stirring them evenly at room temperature, and hydrothermally reacting them at 120-130° C. for 10-11 hours under sealed conditions, then centrifuging, taking the precipitate, washing it and vacuum drying it to obtain the carbon microspheres; The composite comprises mixing carbon microspheres and deionized water, performing ultrasonic oscillation, adding sodium molybdate dihydrate, continuing ultrasonic oscillation, mixing with sodium borohydride, stirring at room temperature for 50-60 minutes, centrifuging, taking a precipitate, washing and vacuum drying to obtain composite microspheres; The mixing, after the iron powder, molybdenum powder, chromium powder, boron powder, carbon powder and yttrium powder are uniformly mixed, is added into a vacuum melting furnace for gas atomization, nitrogen is used as an atomizing gas, the atomization pressure in the gas atomization is controlled to 4-5MPa, and sieving is performed to obtain laser cladding powder; The first-level composite comprises mixing laser cladding powder, molybdenum powder and composite microspheres, ball milling, taking out and drying to obtain first-level composite powder; The primary laser cladding comprises spreading the primary composite powder on the pretreated steel plate, using a pulsed laser for laser cladding, and cleaning the surface of the cladding layer after the laser cladding is completed, cooling naturally, and obtaining a primary laser cladding material; The secondary laser cladding comprises spreading the primary composite powder on the pretreated steel plate, using a pulsed laser for laser cladding, and cleaning the surface of the cladding layer after the laser cladding is completed, cooling naturally, and obtaining a secondary laser cladding material; The second-level composite powder is prepared by mixing the first-level composite powder and the composite microspheres, ball milling, taking out, and drying to obtain the second-level composite powder; The three laser cladding processes are to spread the secondary composite powder on the pretreated steel plate, use a pulsed laser for laser cladding, clean the surface of the cladding layer after the laser cladding is completed, and cool it naturally in the air to obtain a wear-resistant amorphous composite coating.
2. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the preparation of the carbon microspheres, the usage ratio of sucrose, boric acid and deionized water is 155-165 g: 6-6.5 g: 1300-1400 mL.
3. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the composite, the usage ratio of carbon microspheres, deionized water, sodium molybdate dihydrate, and sodium borohydride is 40-42 g: 4000-4500 mL: 70-80 g: 60-65 g; The frequency of the ultrasonic oscillation is 20-25 kHz.
4. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the mixture, the mass ratio of iron powder, molybdenum powder, chromium powder, boron powder, carbon powder and yttrium powder is 54-56:17-18:15-15.5:1.2-1.3:3.4-3.6:3.4-3.6; The mass purity of the iron powder is 99.99%; The mass purity of the molybdenum powder is 99.9%; The mass purity of the chromium powder is 99.99%; The mass purity of the boron powder is 99.9%; The mass purity of the carbon powder is 99.99%; The mass purity of the yttrium powder is 99.5%; The particle size of the cladding powder is 150-400 meshes.
5. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the primary composite, the mass ratio of laser cladding powder, molybdenum powder and composite microspheres is 100:2.1-2.2:2.1-2.2; The molybdenum powder has a mass purity of 99.9% and a particle size of 300 meshes; The ball-to-material mass ratio in the ball mill is 2-3:1, the rotation speed is 300-350rpm, and the ball milling time is 2-2.5h; The temperature during the drying is 110-120° C., and the drying time is 2-2.5 hours.
6. The wear-resistant amorphous composite coating according to claim 1, characterized in that: The pretreatment uses an angle grinder and a wire brush to grind the surface of the steel plate flat, removes surface impurities and oxide scale, and wipes it clean with alcohol to obtain a pretreated steel plate.
7. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the first laser cladding, the thickness of the first-level composite powder is 0.4-0.42 mm; The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min.
8. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the secondary laser cladding, the thickness of the first-level composite powder is 0.3-0.32 mm; The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min; In the preparation of the secondary composite powder, the mass ratio of the primary composite powder to the composite microspheres is 104.2-104.4:0.9-1; The ball-to-material mass ratio in the ball mill is 2-3:1, the rotation speed is 300-350rpm, and the ball milling time is 1.5-2h; The temperature during the drying is 110-120° C., and the drying time is 1.5-2 hours.
9. The wear-resistant amorphous composite coating according to claim 1, characterized in that: In the three laser cladding processes, the thickness of the secondary composite powder is 0.4-0.42 mm. The laser output power in the laser cladding is 600W, the laser duty cycle is 95%, the focal length is 400mm, the pulse voltage is 260-300V, the pulse frequency is 15-20Hz, the pulse width is 2ms, and the argon gas flow rate sprayed on the cladding point is 10L / min.
10. Use of the wear-resistant amorphous composite coating according to any one of claims 1 to 9 in blades of agricultural tools.
Citation Information
Patent Citations
Preparation method for double-layer high-strength corrosion-resistant iron-based amorphous composite coating
CN106835132A
Method for preparing anticorrosion wear-resisting iron-based amorphous coating through laser cladding technology
CN106868496A
Iron-based composite powder for laser cladding layer and preparation method of thick amorphous cladding layer
CN109306433A
Iron-based amorphous nanocrystalline laser cladding composite coating, preparation method and test method
CN109898082A
Strengthening method for improving high-temperature fatigue performance of aviation titanium alloy
CN112662975A